Turkish Translation/Cultural Adaptation and Psychometric Analyses of the Affordances in the Home Environment for Motor Development-Infant Scale (ahemd-Is) - Apaydin, Umut; Eraslan, Rabia; Balikci, Aymen; Elbasan, Buelent (Sage Publications inc, 2023)
In this study we translated the Affordances in the Home Environment for Motor Development-Infant Scale (AHEMD-IS) into Turkish, adapted the instrument culturally, examined its psychometric properties within a Turkish population, and identified its limitations. We administered the AHEMD-IS to families of 65 premature or full-term Turkish infants and repeated this testing for 17 families after one-two weeks to establish test-retest reliability. We calculated the Intraclass Correlation Coefficient (ICC) and Cronbach alpha coefficient to assess reliability, and we evaluated test validity using the Spearman's correlation coefficient and correlations with the Bayley-III motor development score. The Cronbach Alpha coefficient of the questionnaire was 0.846, and, for test-retest reliability, the ICC score was 0.830. The Turkish AHEMD-IS total score was moderately correlated with the Bayley-III fine motor development score (r = 0.469, p < 0.001), the Bayley-III gross motor development score (r = 0.533, p < 0.001), and the Bayley-III total motor development score (r = 0.526, p < 0.001). The Turkish version of the AHEMD-IS was found to be valid and reliable for children born prematurely or at full-term. The use of this questionnaire in Turkey will facilitate the creation of a home environment that will support motor development in children between 3-18 months of age.
Elbasan, Bulent/0000-0001-8714-0214; ZORLULAR, Rabia/0000-0001-9007-553X
Keywords: Motor Development; Affordance; Home Environment; Reliability; Validity